Analysis of User Satisfaction on the Ajaib Investment Application Using the Kano Model and Importance Performance Analysis (IPA) - Aulia Putri; Dedy Setiawan (Universitas Malikussaleh, 2026)
The rapid growth of digital investment applications has increased the importance of evaluating user satisfaction toward fintech services. This study aims to analyze user satisfaction toward the Ajaib investment application using the Kano Model and Importance Performance Analysis based on the dimensions of service quality, trust, and privacy. This study employed a quantitative approach with purposive sampling involving 120 respondents who were active users of the Ajaib application in Indonesia. Data were analyzed using SPSS and Python through validity and reliability testing, Kano Model analysis, IPA analysis, and Kano–IPA integration analysis. The results of the Kano analysis showed that all service attributes were classified into the One-dimensional category, indicating that user satisfaction is directly influenced by service performance. The Reliability attribute obtained the highest Better coefficient (0.904348), showing that improvements in system reliability can significantly increase user satisfaction, while the Unauthorized Secondary Use attribute obtained the highest dissatisfaction effect with a Worse coefficient of -0.84874. The IPA results showed that the Reliability attribute was located in Quadrant I (Concentrate Here), indicating that it requires priority improvement due to its high importance but relatively lower performance. Privacy-related attributes were positioned in Quadrant II (Keep Up the Good Work), indicating that their performance should be maintained. Furthermore, the Kano–IPA integration analysis classified the Reliability attribute into the Defenseless category as the main improvement priority, while privacy attributes were categorized as Major Weapon, indicating that privacy protection is one of the main strengths of the application. This study contributes theoretically by integrating Kano Model and IPA in evaluating digital investment services and practically provides recommendations for improving service quality, trust, and privacy protection in fintech applications.